2022
DOI: 10.1021/acs.analchem.2c02260
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Novel Lipophilic Aggregation-Induced Emission Probes for Revealing the Dynamics of Lipid Droplets during Lipophagy and Ferroptosis

Abstract: Lipid droplets (LDs), as crucial organelles, play a significant role in some physiological processes. Monitoring the concentration of LDs and dynamic behaviors between LDs and other organelles during some physiological processes is important for studying their biological function and medical diagnosis. Herein, we report a series of aggregation-induced emission (AIE) probes AIE-Cbz-LD-C n (n = 1, 3, 5, 7, OMe) based on the conjugation of quinolinemalononitrile (QM) and carbazole for tracking the dynamic changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…3A), including swelling, enlarged and vacuolated nuclei, and increased lipid droplet numbers, consistent with previous reports. [78][79][80] Cell viability assays further revealed that cell damage depended on the TDI-COF concentration and X-ray dose (Fig. 3B).…”
Section: Resultsmentioning
confidence: 92%
“…3A), including swelling, enlarged and vacuolated nuclei, and increased lipid droplet numbers, consistent with previous reports. [78][79][80] Cell viability assays further revealed that cell damage depended on the TDI-COF concentration and X-ray dose (Fig. 3B).…”
Section: Resultsmentioning
confidence: 92%
“…Most hydrophobic fluorophores are suitable for the design of LD probes, and coumarin structure units, similar to Nile red (a commercial LD dye), are also included . However, as shown in Scheme a, currently lipid-targeting probes with an ACQ effect and short wavelengths limited their biological application in vivo imaging. ,, Furthermore, the probe containing the quinoline malononitrile portion had typical AIE properties but lacked water solubility, which was not conducive to LD imaging (Scheme a) . Designing probes with AIE properties, good water solubility, and special targeting of LDs may be beneficial to monitor the process of ferroptosis during AS.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this resulted in a small range of E T 30 values, for THF ( E T 30 37.4) to toluene ( E T 30 33.9), and showed the viability of the probe even in a narrow range. 28…”
Section: Resultsmentioning
confidence: 99%